2020
DOI: 10.1021/acsptsci.0c00131
|View full text |Cite
|
Sign up to set email alerts
|

Virtual and In Vitro Antiviral Screening Revive Therapeutic Drugs for COVID-19

Abstract: The urgent need for a cure for early phase COVID-19 infected patients critically underlines drug repositioning strategies able to efficiently identify new and reliable treatments by merging computational, experimental, and pharmacokinetic expertise. Here we report new potential therapeutics for COVID-19 identified with a combined virtual and experimental screening strategy and selected among already approved drugs. We used hydroxychloroquine (HCQ), one of the most studied drugs in current clinical trials, as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 63 publications
2
66
0
Order By: Relevance
“…Zuclopenthixol, the neuroleptic with the strongest association with sedation and somnolence, has emerged as a compound that shows in vitro inhibition of the severe acute respiratory coronavirus 2 (SARS-CoV-2) pathogen which causes the novel coronavirus disease 2019 (COVID-19) ( Bocci et al, 2020 ). A recent review article reported thioridazine, fluphenazine, perphenazine, chlorpromazine, prochlorperazine inhibits RNA viruses as these phenothiazines inhibit cell-cell fusion, viral replication, clathrin-dependent endocytosis, and entry into cells ( Otręba et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zuclopenthixol, the neuroleptic with the strongest association with sedation and somnolence, has emerged as a compound that shows in vitro inhibition of the severe acute respiratory coronavirus 2 (SARS-CoV-2) pathogen which causes the novel coronavirus disease 2019 (COVID-19) ( Bocci et al, 2020 ). A recent review article reported thioridazine, fluphenazine, perphenazine, chlorpromazine, prochlorperazine inhibits RNA viruses as these phenothiazines inhibit cell-cell fusion, viral replication, clathrin-dependent endocytosis, and entry into cells ( Otręba et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a small-molecule antiviral agent, tegobuvir has been evaluated in clinical trials for COVID-19 [ 38 ], while bisoxatin (DB09219) has been suggested as a potential inhibitor of SARS-CoV-2 spike protein following a computational approach [ 39 ]. Amodiaquine has been found to inhibit SARS-CoV-2 replication in vitro [ 40 ], ketanserin has been suggested as a potential additive drug to improve the ventilation/perfusion mismatch in patients with COVID-19 [ 41 ] and, finally, the anti-HIV drug raltegravir has been proposed as a potential 3CL pro inhibitor following a computational approach [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several psychotropic drugs have been associated with antiviral and antitumor properties, suggesting that they may lower the severity of COVID-19 critical illness [16]. For example, imipramine, clomipramine and the phenothiazine class of drugs have demonstrated efficacy against other viruses, including Ebola, Dengue and West Nile [17][18][19][20]. In addition, thioridazine, another phenothiazine, was found to slow the progression of lung cancers, probably by enhancing antitumor immunity [21].…”
Section: Covid-19 and Psychotropic Drugsmentioning
confidence: 99%